The Notion of International Child Abduction. Commentary to the decision the Provincial Hearing of Valencia, of May 8, 2023 [ECLI:ES:APV:2023:1178] - Sousa Gonçalves, Anabela Susana de (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The wrongful removal or retention of children is governed internationally by the 1980 Hague Convention on the Civil Aspects of International Child Abduction (Hague Convention). The 1980 Hague Convention was drawn up with the aim of protecting or mitigating the effects of wrongful removal or retention of children across borders for the children involved, seeking to ensure the fast return of the child to the country of his/her habitual residence, through a system cooperation between central authorities. The decision of the Provincial Hearing of Valencia, of May 8, 2023, at the origin of this commentary, is based on the existence, or not, of a situation of international child abduction, or wrongful removal or retention of children. This will be the concept that is going to be explored in the present commentary.
Keywords: International child abduction; unlawful retention or removal of children; 1980 Hague Convention